Practicing psychologists’ accounts of demand avoidance and extreme demand avoidance in children and adolescents - Haire, Lauren; Symonds, Jennifer E.; Senior, Joyce; Pace, Ugo (Frontiers in Education, 2023)
The construct of pathological or extreme demand avoidance (EDA) is used to describe the experience of avoiding demands and having an extreme need for control. However, the EDA construct is contested by researchers and educational psychology practitioners. To investigate the utility and validity of the construct of EDA, this qualitative study explored psychologists’ experience and conceptualisation of demand avoidance and extreme demand avoidance, and their approach to working with children and adolescents who avoid demands. Online semi-structured interviews were conducted with twelve psychologists (female = 9) working in private, education and disability services. Thematic analysis yielded six themes: (i) reason for the psychologists’ involvement, (ii) psychologists understanding of child’s presentation, (iii) psychologists’ focus in supporting the child, (iv) challenges for psychologists, (v) enablers for psychologists and (vi) success for psychologists. Results indicated that psychologists do not view the construct of EDA as necessary for their work and achieve success with children who avoid demands by drawing on range of approaches focusing on the underlying needs of those children.